Respuesta :
Answer:
a. [tex]x = 6d^5 - 2c^3d^2 + 5c^2d^3 - 12cd^4 + 8[/tex]
Step-by-step explanation:
Given that
[tex]8d^5 + 3c^3d62 + 5c^2d^3 - 4cd^4 + 9[/tex]
Now
if one is added i.e.
[tex]2d^5 - c^3d^2 + 8cd^4 + 1[/tex]
Now let us assume the other polynomial be x
So,
[tex]8d^5 + 3c^3d62 + 5c^2d^3 - 4cd^4 + 9 = x + (2d^5 - c^3d^2 + 8cd^4 + 1)\\\\x = 8d^5 + 3c^3d62 + 5c^2d^3 - 4cd^4 + 9 - (2d^5 - c^3d^2 + 8cd^4 + 1)\\\\[/tex]
[tex]x = (8d^5 - 2d^5) + (-3c^3d^2 + c^3d^2) + 5c^2d^3+ (-4cd^4-8cd^4) + (9-1)\\\\x = 6d^5 - 2c^3d^2 + 5c^2d^3 - 12cd^4 + 8[/tex]
Answer:
a
Step-by-step explanation:
just use it mannnn